On the fitness of informative cues in complex environments. (21st October 2021) - Mafessoni, Fabrizio; Lachmann, Michael; Gokhale, Chaitanya S.
Highlights: We extend evolutionary information theory approaches to more realistic scenarios. Mutual information always constrains the fitness benefit of informative cues. An approximate upper bound to the fitness of informative cues can often be calculated. Even when bet-hedging evolves, often organisms do not adopt all possible phenotypes. Complex patterns of bet-hedging evolve along environmental gradients. Abstract: To be able to deal with uncertainty is of primary importance to most living organisms. When cues provide information about the state of the environment, organisms can use them to respond flexibly. Life forms have evolved complex adaptations and sensory mechanisms to use these environmental cues and extract valuable information about the environment. Previous work has shown a theoretical limit to the amount of fitness benefit possible to be extracted from the cues. We show that the previously used information theoretical approaches can be generalised to scenarios involving any potential relationship between the number of possible phenotypes and environmental states. Such cases are relevant when physiological constraints or complex ecological scenarios lead to the number of environmental states exceeding potential phenotypes. We illustrate cases in which these scenarios can emerge: along environmental gradients, such as geographical transects or complex environments, where organisms adopt different bet-hedging strategies, switching stochastically between phenotypes or developing intermediate ones. In conclusion, we develop an information-theoretic extensible approach for investigating and quantifying fitness in ecological studies.